The Influence of Work Motivation, Work Environment and Work Discipline on the Performance of Employees of the Human Resources Development and Personnel Agency of North Toraja Regency - Matana, Febriyanti Arung; Pundissing, Rati; Pagiu, Chrismesi (Universitas Negeri Makassar, 2024)
The aim of this study is to determine whether there is an influence of Work Motivation, Work Environment, and Work Discipline on Employee Performance at the Human Resources and Development Agency of Toraja Regency. The data collection procedures in this study include observation, questionnaires, and documentation. The method used in this study is a quantitative method with multiple linear regression analysis processed using SPSS 26. The sampling technique used by the researcher is the census method (total sampling), where the entire population of 31 members is used as the sample. The t-test results show that for the Work Motivation variable, the t-value is greater than the t-table value (10.860 > 2.05183), for the Work Environment variable, the t-value is greater than the t-table value (3.980 > 2.05183), and for the Work Discipline variable, the t-value is greater than the t-table value (3.233 > 2.05183). The conclusion of this study is that Work Motivation, Work Environment, and Work Discipline have a positive and significant influence on employee productivity.